2021
DOI: 10.1155/2021/7522487
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Hyperandrogenism and Ovulatory Dysfunction Are Not Associated with His1058 C/T SNP (rs1799817) Polymorphism of Insulin Receptor Gene Tyrosine Kinase Domain in Kashmiri Women with PCOS

Abstract: Background. Polycystic ovary syndrome (PCOS) is the most common endocrine metabolic disorder affecting premenopausal women. Besides primary features like anovulation, hyperandrogenism, and polycystic ovaries, women with PCOS present with multiple metabolic, cardiovascular, and psychological disorders. The etiology is multifactorial and the different genetic variants are suggested to play an important role in pathogenesis. Insulin resistance is a ubiquitous finding in PCOS and SNPs in genes involved in the insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A gene susceptibility test for PCOS may reduce the risk of obesity, cardiovascular disease, and T2DM in the long run [48]. SNPs in genes related to insulin signaling are potential candidates to explain PCOS's clinical manifestations since insulin resistance is a common finding in the disorder [14]. Even though many PCOS women are more likely to develop insulin resistance, poor glucose tolerance, and pancreatic dysfunction, which increases their risk of developing T2DM later in life, there may be fundamental differences in the mechanism of insulin resistance in T2DM and PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A gene susceptibility test for PCOS may reduce the risk of obesity, cardiovascular disease, and T2DM in the long run [48]. SNPs in genes related to insulin signaling are potential candidates to explain PCOS's clinical manifestations since insulin resistance is a common finding in the disorder [14]. Even though many PCOS women are more likely to develop insulin resistance, poor glucose tolerance, and pancreatic dysfunction, which increases their risk of developing T2DM later in life, there may be fundamental differences in the mechanism of insulin resistance in T2DM and PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…IGF2BP2 is encoded by the IGF2BP2 gene located on chromosome 3q27 [12,13]. PCOS is characterized by insulin resistance; therefore, SNPs linked to the insulin signaling pathways may contribute to the development of PCOS's clinical features [14]. Two SNPs, the rs11705701 G/A (GRCh38.p12, minor allele frequency [MAF] = 0.49) and rs1470579 A/C (GRCh37.p13, MAF = 0.45), have already been correlated to T2DM susceptibility in other races [15].…”
mentioning
confidence: 99%
“…It has been found that IRS-1 G972R polymorphism is directly associated with the insulin receptors and inhibits autophosphorylation of INSR. This association has been found to occur in the β subunit of INSR that includes the tyrosine kinase domain at residues 966 and 1271 [ 46 ]. This interaction also involves INSR His1058 residue, indicating a relationship between INSR C/T polymorphism and IRS-1 Gly972Arg polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Significant internal factors are involved in the development of PCOS-related insulin resistance, although in some cases, it may only be acquired due to exogenous obesity. The root cause of PCOS is related to defects in intracellular insulin signaling downstream of the insulin receptor, which includes the hyperphosphorylation of serine residues on the insulin receptor substrate 1 (IRS-1) protein, which then binds to the insulin receptor and initiates insulin-specific intracellular responses (82)(83)(84). Insulin resistance has been observed not only in peripheral tissues of PCOS patients, such as adipocytes and skeletal muscle, but also in fibroblasts and ovarian granulosa and theca cells.…”
Section: Elevated Insulin Resistance In the Development Of Pcosmentioning
confidence: 99%